Analysis of the Thermal Properties of GaInAs Quantum Cascade Lasers - Concepción, Omar; Abelenda, Arturo; González, J. C.; Sánchez-Colina, María (Revista Cubana de Física; Vol 32 No 1 (2015), 2015)
A study of the temperature distribution of GaInAs/AlInAs quantum cascade lasers (QCLs) is presented. The heat conduction equation was solved using a finite-element method and a two-dimensional anisotropic heat-flow model. The thermal resistance (R th ) was calculated and compared with experimental results reported by other authors obtaining a good agreement. Comparison of heat dissipation in a double channel (DC) and buried heterostructure (BH) was performed analyzing the influence of the ridge height. The effect of materials used as: heat-sink, capping and insulation layer were evaluated. The results show that a DC-QCL with a deep-ridge waveguide, using: InP as top capping layer, Si 3 N 4 as insulation layer, and graphene as heat-sink presents a better performance than a BH-QCL.